Lactiplantibacillus plantarum Ameliorated Morphological Damage and Barrier Dysfunction and Reduced Apoptosis and Ferroptosis in the Jejunum of Oxidatively Stressed Piglets - Yu Liu; Junmeng Yuan; Wenshuo Xi; Zhisheng Wang; Huawei Liu; Kai Zhang; Jinshan Zhao; Yang Wang (Animals)
Oxidative stress induces apoptosis and ferroptosis, leading to intestinal injury of piglets. Lactiplantibacillus plantarum P8 (P8) has antioxidant capacity, but its roles in intestinal apoptosis and ferroptosis remain unclear. Here, 24 weaned piglets were assigned to three treatments: control (Con), diquat injection (DQ), and P8 supplementation + DQ injection (DQ + P8). The results showed that the increased jejunal oxidative stress, jejunal morphology impairment, and barrier dysfunction in the DQ-treated piglets were decreased by P8 supplementation. TUNEL and apoptosis-related gene expressions showed increased jejunal apoptosis of DQ-treated piglets; however, reduced apoptosis was observed in the DQ + P8 group. In addition, the mitochondrial morphology and ferroptosis-related gene expressions indicated elevated jejunal ferroptosis in the DQ-treated piglets, and the DQ + P8 treatment attenuated the ferroptosis. Transcriptome identified various differentially expressed genes (DEGs) between different treatments. KEGG analysis indicated that the DEGs were enriched in the PI3K-AKT, NF-κB, and apoptosis pathways. The expressions of key DEGs and key proteins in the PI3K-AKT and NF-κB pathways were further verified. In summary, our results indicate that P8 supplementation ameliorated jejunal oxidative stress, morphological damage, barrier dysfunction, apoptosis, and ferroptosis in the DQ-treated piglets. Moreover, the beneficial effect of P8 may be related to the regulation of PI3K/AKT and NF-κB pathways.